Active Navigation in a Hepatitis B Program: Screening, Vaccination and Patient Assistance for Asian Americans in Michigan - Janilla Lee (Archives of Hepatitis Research - Peertechz Publications, 2018)
Background: Hepatitis B (HBV) is one of the greatest health disparities among Asian Americans. A team of volunteers in Southeast Michigan has studied HBV among Asian Americans in Michigan for 10 years. The study looked at prevalence of HBV among Asian Americans in Michigan, and the effectiveness of programs that included screening, vaccination and patient navigation. Method: The team offered free screening, and then offered free vaccination to those never infected by the virus among the screened population. The project also offered confirmed patients disease navigation, helping them to obtain a minimum of one comprehensive liver test, and follow-up care. Results: The screening results: 6.4% had chronic hepatitis B, 50.1% had the antibody, and 43.5% were never infected, nor vaccinated. Free vaccination was offered to eligible participants and only 46.0% accepted it. For the free patient navigation, the rate of acceptance (take-rate) was only 43.8%. Conclusion: For every program in this project, education was a component. But at the end, lack of education still seems to be a major concern. Many participants would not take our offer of free vaccine for prevention or help with further steps to take care of his/her disease.  This study points to a need for an innovative public health education program for Hepatitis B.